Implementasi Model Pembelajaran CTL (Contextual Teaching And Learning) untuk Meningkatkan Hasil Belajar IPA - Ariawan, Ida Bagus Kade Mester; Lestari, Nyoman Ayu Putri; Dharma, I Made Aditya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This classroom action research aims to improve science learning outcomes on light material and its properties for fifth grade students in the first semester of SD Negeri 3 Batuagung for the 2020/2021 academic year through the application of the CTL learning model. (Contextual Teaching and Learning). The subjects of this study were 25 students of class V, consisting of 11 male students and 14 female students. Data on student learning outcomes was obtained using the test method with a set of learning outcomes test instruments. The data obtained were analyzed using quantitative descriptive data analysis.The results of data analysis show the application of the CTL learning model (Contextual Teaching and Learning) can improve science learning outcomes in students. This is indicated by the increase in the average and classical quantification of students' science learning outcomes from pre-cycle to cycle II. Theaverage student learning outcomes increased by 4.68 from the pre-cycle to the first cycle, from 65.40 to 70.08. Then it increased by 15 points from pre-cycle to cycle II, from 65.40 to 80.40 and increased by 10.32 points from cycle I to cycle II, from 70.08 to 80.40. Meanwhile, the percentage of students' classical completeness also increased by 12% from pre-cycle to cycle I, from 40% to 52%. Then it increased by 52% from pre-cycle to cycle II, ie from 40% to 92%. And increased 40% from cycle I to cycle II, ie from 52% to 92%.